2015
DOI: 10.1038/ncomms7622
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale determination of absolute phosphorylation stoichiometries in human cells by motif-targeting quantitative proteomics

Abstract: Our ability to model the dynamics of signal transduction networks will depend on accurate methods to quantify levels of protein phosphorylation on a global scale. Here we describe a motif-targeting quantitation method for phosphorylation stoichiometry typing. Proteome-wide phosphorylation stoichiometry can be obtained by a simple phosphoproteomic workflow integrating dephosphorylation and isotope tagging with enzymatic kinase reaction. Proof-of-concept experiments using CK2-, MAPK- and EGFR-targeting assays in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
120
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 36 publications
11
120
0
3
Order By: Relevance
“…Thus, it has been demonstrated that His and Asp phosphorylation regulate the functions of pathogenesis, such as adherence, motility, enhancement of toxicity, quorum sensing, capsule formation, and drug resistance (100). Recently, in cancer drug development studies, it has been suggested that changes in phosphorylation stoichiometry are helpful for characterizing the kinase-dependent pathway in gefitinib-resistant lung cancer cells (101). Our study showed that Ser-90 phosphorylation of AmpC may be part of the kinase/ phosphatase machinery conferring imipenem resistance, ␤-lactamase activity, and the ability to neutralize imipenem in A. baumannii.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, it has been demonstrated that His and Asp phosphorylation regulate the functions of pathogenesis, such as adherence, motility, enhancement of toxicity, quorum sensing, capsule formation, and drug resistance (100). Recently, in cancer drug development studies, it has been suggested that changes in phosphorylation stoichiometry are helpful for characterizing the kinase-dependent pathway in gefitinib-resistant lung cancer cells (101). Our study showed that Ser-90 phosphorylation of AmpC may be part of the kinase/ phosphatase machinery conferring imipenem resistance, ␤-lactamase activity, and the ability to neutralize imipenem in A. baumannii.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, ZNF687 res373-382 was synthesized, in which we phosphorylated Ser374 and Thr377 (at P−6 and P−3, respectively, with respect to the O-GlcNAc site), and the percentage O-GlcNAcylation on the phosphopeptides was compared with that of the unmodified peptide ( Table 2). The phosphosites were chosen based on their reported detection (32). Consistent with our previous data on CRMP2 (SI Appendix, Fig.…”
Section: Reciprocal Interplay Does Not Occur On Ser/thr Sites Targetementioning
confidence: 96%
“…In addition, NQO1 can undergo post-translational modifications such as phosphorylation [42] and ubiquitination [43]. It has been shown previously that phosphorylation and other post-translational modifications of RBPs including HuR, BRF1, TTP, KSRP, TIAR/TIA-1 have been linked to changes in their subcellular localization and their association with target mRNAs [44].…”
Section: Discussionmentioning
confidence: 99%